1992
DOI: 10.1111/j.1348-0421.1992.tb02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clostridium botulinum Type E and Coexistence of C. botulinum Nonproteolytic Type B in the River Soil of Japan

Abstract: Soil samples from 98 sites in the whole systems of four rivers in Japan were examined for the presence of Clostridium botulinum . Type E organism was prevalently shown throughout the whole river systems including upper part ; detection rates of type E toxin in soil culture ranged from 33 to 82% . This type was also detected in soil of adjacent mountainous district . Type B and C toxins were detected at 7% and 9% of the sites examined , respectively. C, botulinum type E and nonproteolytic type B strains were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…For example, in 1991, an epidemic of botulism was reported from Egypt, in which 99 individuals were intoxicated and 18 of them died because of traditional, smoked, salted fish consumption. Studies in China, France, Canada, Alaska and Japan showed botulism poisoning following ingestion of raw, salted, smoked and vacuumed fish [7,9,10,21,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in 1991, an epidemic of botulism was reported from Egypt, in which 99 individuals were intoxicated and 18 of them died because of traditional, smoked, salted fish consumption. Studies in China, France, Canada, Alaska and Japan showed botulism poisoning following ingestion of raw, salted, smoked and vacuumed fish [7,9,10,21,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Type E, in contrast, is found in aquatic environments, sea food and marine sediments. This toxin is a known source of botulism--and has been reported internationally [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of botulinum toxin-producing organisms in soil was demonstrated by the method described by Yamakawa et al [7]. Ten 1-g portions of each soil specimen were inoculated into 10 tubes containing a chopped meat-glucose (CMG) medium [8] and incubated anaerobically at 30°C for 5 days.…”
Section: Isolation Of Neurotoxigenic C Butyricummentioning
confidence: 99%
“…This then significantly raises the risk of clostridial diseases [2,11]. The incidence and distribution of clostridial disease have also been shown to coincide with locations near river and stream systems in Japan and the United Kingdom [19,22]. It is worth noting that the case numbers of clostridial diseases usually increase after a heavy rainfall.…”
mentioning
confidence: 99%
“…They have been reported worldwide in Asian, African and European countries including Japan, Zambia, Nigeria and United Kingdom [2,9,19,22]. Clostridia are widely distributed in nature and are found in soil as well as freshwater and marine sediments throughout the world.…”
mentioning
confidence: 99%